Implementing effective communication among Hajj Pilgrims / Liza Marziana Mohammad Noh ... [et al.] - Mohammad Noh, Liza Marziana; Yook Ngor, Phang; Abdul Karim Zamri, Norena; Mohammad, Norazlinda; Idris, Nurkhazilah; Alias, Aidah; Radzi, Raha (Faculty of Art and Design, 2020)
During the Hajj season, the pilgrims will perform their Hajj in the Holy Land of Mecca, Saudi Arabia houses. Performing hajj is the fifth principle of Islam and it is compulsory for all Muslims who have the physical and financial capability to perform Hajj at least once in their lifetime. For that, health quality is important to be preserved because it not only helps clear the flow of Hajj but also ensures the safety of the pilgrims' journey. This study aims to evaluate the effectiveness of the communicative strategy by Utas Travel agency in creating the awareness of healthcare services for the pilgrims. Data analysis will be employing the qualitative approach. Interviewing will be adopted onto the pilgrims who have performed Hajj for a few years ago and for the first time. Interview will be done onto about 50 pilgrims using open-ended questions and data will be analysed using thematic analysis. The research outcome will benefit Utas Travel agency in identifying an effective communicative strategy in creating a healthcare service model awareness for pilgrims. This study can add to the pool of knowledge. The purpose of the study is therefore to develop an effective communication model for promoting the Hajj sector.